1999
DOI: 10.1080/08035259950169206
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alpha in viral and bacterial gastroenteritis: a comparison with C-reactive protein and interleukin-6

Abstract: The aim of the study was to identify serum markers able to differentiate bacterial and viral origin in acute diarrhoea. Interferon-alpha (INF-alpha), C-reactive protein (CRP) and interleukin-6 were determined on admission in the sera of 119 children aged between 1 mo and 14 y who were hospitalized for rotavirus (n = 60) or bacterial diarrhoea (Salmonella spp. 39 cases, Shigella spp. 15 cases, Campylobacter jejuni 5 cases). CRP concentration was >10 mg/l in 48.3% of children with viral gastroenteritis and 86.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Other enteroviruses including astroviruses, noroviruses, and adenoviruses are also frequent causes of diarrhea episodes in children [38]. Th1 responses and inflammation play important roles in anti-enteroviral immunity [39,40] and are associated with local production of IFN-␣ [41,42]. It is therefore conceivable that IFN-␣ production as a result of a viral infection would lead to a shift toward Th1 responses and reinstruct previously tolerogenic DCs to prime gluten-specific T cells and support inflammation instead of sustaining oral tolerance.…”
Section: Type I Interferons and Virusesmentioning
confidence: 99%
“…Other enteroviruses including astroviruses, noroviruses, and adenoviruses are also frequent causes of diarrhea episodes in children [38]. Th1 responses and inflammation play important roles in anti-enteroviral immunity [39,40] and are associated with local production of IFN-␣ [41,42]. It is therefore conceivable that IFN-␣ production as a result of a viral infection would lead to a shift toward Th1 responses and reinstruct previously tolerogenic DCs to prime gluten-specific T cells and support inflammation instead of sustaining oral tolerance.…”
Section: Type I Interferons and Virusesmentioning
confidence: 99%
“… † Direct comparison between viral and bacterial infections revealed higher circulating levels in viral infections [74]. N.D.: not detected.…”
Section: Plasma Inflammatory Profiles In Viral and Bacterial Infectionsmentioning
confidence: 99%
“…A recent study of total human peripheral blood mononuclear cells (PBMCs) exposed to RRV or human rotavirus indicated that both myeloid DCs and pDCs are susceptible to infection, and that infection results in the secretion of IFNa, presumably from pDCs [42]. While increased levels of IFNa have also been correlated with a positive clinical outcome in infected children [43,44], several rotaviruses, including RRV, have recently been demonstrated to antagonize the production of type I IFN through the degradation of interferon regulatory factors (IRF)3, IRF5, and IRF7, and the inhibition of NFkB activation, by a viral nonstructural protein, NSP1 [45,46,47,48].…”
Section: Introductionmentioning
confidence: 99%